2016
DOI: 10.1167/iovs.16-19548
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Phase Retardation in Filtering Blebs Using Polarization-Sensitive Optical Coherence Tomography

Abstract: An increase in phase retardation preceded deterioration of bleb function. The change in phase retardation may provide a prognostic metric for bleb function in the early stage after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
3
7
1
Order By: Relevance
“…Phase retardation images might be effective for evaluating mild fibrotic changes during the early stage after surgery, as previously reported. This finding is consistent with our previous report that phase retardation images provide an estimated prognostic value for filtering bleb function during the early stage after glaucoma surgery 18 , 19 .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Phase retardation images might be effective for evaluating mild fibrotic changes during the early stage after surgery, as previously reported. This finding is consistent with our previous report that phase retardation images provide an estimated prognostic value for filtering bleb function during the early stage after glaucoma surgery 18 , 19 .…”
Section: Resultssupporting
confidence: 93%
“…A large hyporeflective area was considered to represent a small amount fibrosis, which correlated with the function of the blebs 12 . The current study and previous studies revealed that the reflectivity on intensity images did not always correlate with tissue fibrosis 18 , 19 , 22 . We recently reported that PS-OCT was useful for evaluating bleb fibrosis after glaucoma filtration surgery using two types of birefringent imaging: phase retardation and local birefringence 18 , 19 , 22 .…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations